Радянські війська й Угорська революція 1956 року в навчальних виданнях для вишів України - Вароді Наталія; Váradi Natália; Natalia Varadi (Київський університет імені Бориса Грінченка, 2021)
Резюме. У статті визначено основні тенденції висвітлення ролі радянських військ під час Угорської революції 1956 р. в підручниках і навчальних посібниках для вишів, виданих у незалежній Україні. Зважаючи на когнітивний і регулятивний вміст останніх, зроблено порівняння авторського бачення обставин, за яких радянські війська втрутились у революцію, їхні дії в Угорщині й втрати. З огляду на рефлексивний чинник проаналізовано, наскільки згадки про участь цих військ у революції оцінкові й / або емоційно забарвлені.

Abstract. Educational publications are an integral part of the historiographical process. Their content is affected by academic traditions. Textbooks are also a multilayer cultural product and form of expression of critical thinking of historians. They also influence the choice of learning strategy. The educational text contents cognitive, regulatory and reflexive information. Thus, it is important as the contradictory phenomena and events of the past, such as the actions of Soviet forces in Hungary of 1956, are conveyed in publications of this kind. To consider how these actions are presented in textbooks for high schools is important for a theoretical understanding of the level of these educational publications and to outline the prospects for their improvement. The subject of the study is the interpretation of the role of Soviet forces during the Hungarian Revolution of 1956 in textbooks and manuals for universities published in the independent Ukraine. The article is based on the principles of historicism and objectivity; analysis, synthesis, comparative historical method. The main features of the research are the location and interrogation of all the appropriate educational publications to dissolve a problem. The participation of Soviet troops in the Hungarian Revolution of 1956 is covered in a similar way in the analysed textbooks and manuals except at first the losses of the Soviets. The story is slightly misrepresented in two manuals. O. Ivanytska covered the topic in the most balanced way. Emotional expressions do not interfere with the achievement of the main educational goal of the textbooks and manuals. There are no relations between their content and timing. In general, it is desirable for students to study all the analysed educational publications at the same time.
Soviet Forces and the Hungarian Revolution of 1956 in Educational Publications for Ukrainian Universities
Keywords: підручник; навчальний посібник; Угорська революція 1956 р.; радянські війська; когнітивний вміст; регулятивний вміст; рефлексивний вміст